Penelitian Kualitatif : Hubungan Kepemimpinan, Kecerdasan Emosional, dan Kinerja - Joni Prihatin (Jurnal Strategi Bisnis Teknologi, 2025)
Leadership is not just about being a leader within an organization. It requires effective communication strategies and approaches. However, leadership changes when there are weaknesses in implementing communication methods with the team. Internal conflict, pressure from leaders, leadership style, and a leader's personality in facing challenges and problems are all factors. The purpose of this study is to deeply understand the relationship between leadership, emotional intelligence, and performance in an organizational context through a qualitative approach. The research method is derived from references in books and journals related to the topic under study. This study explores how leadership styles, interact with dimensions of emotional intelligence, including self-awareness, self-regulation, empathy, intrinsic motivation, and social skills, to influence individual and team performance. The study found that leaders with high emotional intelligence tend to implement an adaptive and inclusive leadership approach, create a conducive work climate, strengthen trust, and increase member engagement and productivity. The findings also reveal that emotional intelligence is not merely a supporting competency but also functions as a critical moderator of leadership effectiveness in achieving performance. This research provides theoretical contributions by enriching a holistic understanding of the psychosocial dynamics of leadership, as well as practical implications for the development of emotional intelligence-based leadership training programs through detailed quantitative and object-based research.